2017
DOI: 10.1590/0104-6632.20170343s20150617
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the leachability of nitrate, phosphorus and heavy metals from soil using waste material

Abstract: -Contaminants like nitrate (NO 3 ), phosphorus (P) and heavy metals in water are often associated with agricultural activities. Various soil and water remediation techniques have been employed to reduce the risk associated with these contaminants. A study was conducted to examine the extent of leaching of heavy metals (Cd, Ni, Pb and Cr), NO 3 and P. For this purpose sandy and silt loam soils were amended with different waste materials, namely wood ash, solid waste ash, vegetable waste, charcoal, and sawdust. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Four soils were contaminated by the addition of charcoal, so application of charcoal causes to improves microbial biomass and its activity, and also nutrient availability [12]. Amount of phosphorus and nitrate concentrations in the leachate also significantly decreased by adding each of the charcoal, sawdust and wood ash [13]. Other previous study reported that soil carbon as fulvic (10 to 20 cm) and humic acids (10 to 30 cm), and especially as humin (0 to 5 cm), increased due to increase charcoal which may be occurred by the role of the charcoal [14].…”
Section: Introductionmentioning
confidence: 99%
“…Four soils were contaminated by the addition of charcoal, so application of charcoal causes to improves microbial biomass and its activity, and also nutrient availability [12]. Amount of phosphorus and nitrate concentrations in the leachate also significantly decreased by adding each of the charcoal, sawdust and wood ash [13]. Other previous study reported that soil carbon as fulvic (10 to 20 cm) and humic acids (10 to 30 cm), and especially as humin (0 to 5 cm), increased due to increase charcoal which may be occurred by the role of the charcoal [14].…”
Section: Introductionmentioning
confidence: 99%
“…Excess intake of NO 3 ions can cause serious health problems, due to the fact that NO 3 -is easily transformed to NO 2 in the human body. This causes an oxygen deficiency in the blood, mainly in children, called methemoglobinemia [4,5]. In addition, NO 2 -are precursors of carcinogenic nitrosamines [6].For this reason, maximum tolerable limits have been established for these anions through different legislations [7][8][9] in water for human consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Industrial sites, formerly associated with gas production and petroleum refining, are often highly contaminated with polycyclic aromatic hydrocarbons (PAHs), and the remediation of such sites poses a great challenge 3. PAHs tend to be strongly attracted by the organic matter in the soil and might remain there for many years 3–5. Intermolecular chemical interactions between PAHs and soil surface take place through Van der Waals forces, bipolar or hydrogen bonds, covalent bonds, ion exchange or superficial sorption 6.…”
Section: Introductionmentioning
confidence: 99%